Examination of the relationship between treatment motivation and neuropsychological test performance in patients with alcohol dependency - Eleman, Burçin; Akvardar, Yıldız; Koçuk, Neşe; Akdede, Berna Binnur (Journal of Dependence, 2015)
Objective: Motivation is the main mechanism underlying why and how people change their behavior. Some research studying the effects of treatment motivation in alcohol addiction focuses on the effects of the cognitive functions of motivation. The purpose of this research is to examine treatment motivation of patients with alcohol dependency, their neuropsychological test performance, and the relationship between them.Method: The sample of this study consists of 21 male patients with alcohol addiction, according to DSM-IV criteria. Participants in the study were assessed using the following instruments: Treatment Motivation Questionnaire (TMQ), Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES), Multidimensional Perceived Social Support Scale, Hamilton Depression and Anxiety Scales, and a neuropsychological test battery that assesses a patient’s cognitive function in many different areas.Results: Study results indicate that there is a significant correlation between treatment motivation and executive functions (r: .46 p: .04). There is also significant correlation between seeking interpersonal help and verbal fluency (r: -.48 p: .03).Conclusion: These results support that the idea that cognitive functions have an important effect on treatment motivation and readiness to change.
Keywords: Treatment motivation; alcohol dependence; readinesstochange; cognitive functions; neuropsychological tests